Development of Architecture and Design Direction the Significance of Colors in School Classrooms (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
No one denies that school classrooms, their design and building project, designed for learning, play an important role in the effectiveness of the educational process. Researchers conducted research on the impact of design environment in educational institutions and obtained the main results.